2015
DOI: 10.1186/s12891-015-0513-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety and performance of Hydros and Hydros-TA for knee osteoarthritis: a prospective, multicenter, randomized, double-blind feasibility trial

Abstract: BackgroundStudies have evaluated the concomitant use of hyaluronan (HA) with steroids, anti-inflammatory drugs and analgesic agents in an attempt to magnify the extent and duration of pain relief due to knee osteoarthritis. To date there has not been an intra-articular combination therapy available for relief of knee osteoarthritis symptoms – one that combines the fast acting onset of symptom relief provided by a corticosteroid with the long-lasting symptom relief provided by HA in a single injection. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 17 publications
(19 reference statements)
0
48
1
3
Order By: Relevance
“…[391] A systematic review, which included data from six randomized controlled trials comparing the effectiveness of PRP with other intra-articular injections, exercise, or analgesia for a minimum of 6 months PRP produced statistically significant improvements in WOMAC scores for up to 12 months. [393][394][395] www.advancedsciencenews.com www.advtherap.com HA hydrogel n/a Dexamethasone Cortocosteroid [310] Adant (Suprahyal) 500-1000 Tenoxicam NSAID [311] Variofill (Adoderm, Langenfeld, Gmbh) HMWCR Diclofenac Sodium clodronate Triamcinolone acetonide Ropivacaine HCl NSAID DMOAD Cortocosteroid Anaesthetic [312] [ 313] Hydros, Hydros-TA HMW Triamcinolone acetonide Cortocosteroid [314] Cingal 1900 Triamcinolone acetonide Cortocosteroid [315] Hylan GF-20 HMWCR Triamcinolone acetonide Cortocosteroid [316] HA solution 800 Mannitol Anti-oxidant [317] Go-on matrix Ostenil Plus 1500 Mannitol Anti-oxidant [320] Happyvix 1500 Mannitol Anti-oxidant [320] Happycross 1500 Mannitol Anti-oxidant [320] Synolis V-A 2000 Sorbitol Anti-oxidant [320] HA 4AR conjugate 2200 4 aminoresorcinol Anti-oxidant [321] Ostenil 1000-2000 l-glutathione Anti-oxidant [322] Arthrum HCS 2800 CS GAG [320] Surgical Syonium 2800 CS GAG [320] HA-sCT conjugate 200 Salmon calcitonin DMOAD [323] HA ADAMTS inhibitor n/a ADAMTS inhibitor DMOAD [324] HA hydrogel 60-120 Doxycycline DMOAD [296] Hanox Hanox M-XL 1500 n/a Cortivazol Triamcinolone hexacetonide Mannitol + lidocaine clorhydrate Cortocosteroid Cortocosteroid Anti-oxidant + local anaesthetic [325] n/a, not available; HMW, high molecular weight; HMWCR, high molecular weight cross-linked. [393][394][395] www.advancedsciencenews.com www.advtherap.com HA hydrogel n/a Dexamethasone Cortocosteroid [310] Adant (Suprahyal) 500-1000 Tenoxicam NSAID [311] Variofill (Adoderm, Langenfeld, Gmbh) HMWCR Diclofenac Sodium clodronate Triamcinolone acetonide Ropivacaine HCl NSAID DMOAD Cortocosteroid Anaesthetic …”
Section: Therapeutic Properties Of Platelet Rich Plasmamentioning
confidence: 99%
“…[391] A systematic review, which included data from six randomized controlled trials comparing the effectiveness of PRP with other intra-articular injections, exercise, or analgesia for a minimum of 6 months PRP produced statistically significant improvements in WOMAC scores for up to 12 months. [393][394][395] www.advancedsciencenews.com www.advtherap.com HA hydrogel n/a Dexamethasone Cortocosteroid [310] Adant (Suprahyal) 500-1000 Tenoxicam NSAID [311] Variofill (Adoderm, Langenfeld, Gmbh) HMWCR Diclofenac Sodium clodronate Triamcinolone acetonide Ropivacaine HCl NSAID DMOAD Cortocosteroid Anaesthetic [312] [ 313] Hydros, Hydros-TA HMW Triamcinolone acetonide Cortocosteroid [314] Cingal 1900 Triamcinolone acetonide Cortocosteroid [315] Hylan GF-20 HMWCR Triamcinolone acetonide Cortocosteroid [316] HA solution 800 Mannitol Anti-oxidant [317] Go-on matrix Ostenil Plus 1500 Mannitol Anti-oxidant [320] Happyvix 1500 Mannitol Anti-oxidant [320] Happycross 1500 Mannitol Anti-oxidant [320] Synolis V-A 2000 Sorbitol Anti-oxidant [320] HA 4AR conjugate 2200 4 aminoresorcinol Anti-oxidant [321] Ostenil 1000-2000 l-glutathione Anti-oxidant [322] Arthrum HCS 2800 CS GAG [320] Surgical Syonium 2800 CS GAG [320] HA-sCT conjugate 200 Salmon calcitonin DMOAD [323] HA ADAMTS inhibitor n/a ADAMTS inhibitor DMOAD [324] HA hydrogel 60-120 Doxycycline DMOAD [296] Hanox Hanox M-XL 1500 n/a Cortivazol Triamcinolone hexacetonide Mannitol + lidocaine clorhydrate Cortocosteroid Cortocosteroid Anti-oxidant + local anaesthetic [325] n/a, not available; HMW, high molecular weight; HMWCR, high molecular weight cross-linked. [393][394][395] www.advancedsciencenews.com www.advtherap.com HA hydrogel n/a Dexamethasone Cortocosteroid [310] Adant (Suprahyal) 500-1000 Tenoxicam NSAID [311] Variofill (Adoderm, Langenfeld, Gmbh) HMWCR Diclofenac Sodium clodronate Triamcinolone acetonide Ropivacaine HCl NSAID DMOAD Cortocosteroid Anaesthetic …”
Section: Therapeutic Properties Of Platelet Rich Plasmamentioning
confidence: 99%
“…Several studies investigated combined therapy with corticosteroids in various pathologies, as knee osteoarthritis, stenosing tenosynovitis of fingers flexor tendons, internal derangement of temporomandibular joint, adhesive capsulitis and lateral epicondylitis (Tab. XII) 89,148,[153][154][155][156][157] . Despite the different indications and protocols, all these studies suggested the superiority of the therapeutic association in terms of efficacy (pain reduction) compared to the use of each treatment alone.…”
Section: Combination Therapy With Ha Association With Corticosteroidsmentioning
confidence: 99%
“…Fifty-seven studies (40 RCTs and 17 systematic reviews) were selected 65,78,98,99,101,102,104,107,108,114,136,139,140,148,156,158,159, . Absolute contraindications are represented by hypersensitivity to products, suspect or presence of infections at injection skin site or selected joint, joint inflammatory states.…”
Section: Contraindications and Adverse Effectsmentioning
confidence: 99%
“…The role of intra-articular CS in the development of the acute reactions is somewhat unclear. While CS and HA injections may be used concomitantly to improve the overall functional response [24][25][26] or used 1 week apart to reduce the risk of pseudoseptic arthritis, 22 acute reactions have also been reported following intra-articular CS use. 17 Intra-articular CS injections given before or with HA have been suggested to promote infections.…”
Section: Discussionmentioning
confidence: 99%